Dampak Implementasi Pembelajaran Daring Terhadap Karakter Anak Di Masa Pandemi Covid-19 - Alfi Rohmatul Azizah; Ahmad Samawi; Nur Anisa (Universitas Al-Hikmah Indonesia, 2021)
The COVID-19 pandemic was caused the transformation of the learning system in the world to change rapidly. Learning through the network effects creating childhood's character. The study aims to describe the impact of the implementation of online learning on the character of children generated during the online study using the google classroom and zoom cloud meeting. The study used a qualitative approach with case studies in data collection by observation, interview, questionnaire, and documentary. As a result of this study, it may be noted that there has been a positive and negative effect on the character of children when online study through google classroom and zoom cloud meeting. The positive effect of the implementation of online learning during the covid-19 pandemic is demonstrated with child competence in the use of learning technology and the emergence of certain characteristics such as responsibility, discipline, religion, nationalism, courage, patience, and self-sufficiency. On the other hand, the implementation of online learning causes a drop in child sociability